Open shell dianions likely to be stable in the gas phase with respect to autoionization - YUMAK YAHŞİ, AYŞE (AMER CHEMICAL SOC, 2005)
We address the challenge set by Dreuw and Cederbaum [Dreuw, A.; Cederbaum, L. S. Chem. Rev. 2002, 102, 181-200] to develop a set of small open shell stable dianions. We offer two families of such species, based on a central diradical center with attached anionic sites. Both families achieve dianion stabilization through alternating zones of positive and negative charge. First, quasi-linear systems such as NB(C-2)(n)-Q-(C-2)(n)BN become diradical dianions stable to autoionization in two cases: (a) for Q a divalent (carbene) carbon when n is two or greater and (b) for Q a C-4 ring diradical when n is one or greater. Second, carbenes with certain anionic aromatic substituents can be stable with respect to autoionization. g-Acid substituted carbenes (A(2)Q) have triplet ground states generally. If A is cyclopentadienyl anion stabilized by cyano substitution, the resulting triplet dianion is stable with respect to autoionization. In bisphenyl carbenes the triplet is relatively stabilized when ortho substituents force the system toward D-2d symmetry. The dianion of bis(orthochlorophenyl) carbene produced by para-substitution with BN retains the triplet preference and is stable with respect to autoionization. These results obtained first by density functional calculations in a small basis, B3LYP/6-31 G(d), are confirmed and extended by ROMP2 and CCSD calculations in a more flexible basis, 6-31+G(d). DFT has a systematic bias against systems with excess electrons, which is paradoxically a virtue in the screening of candidate dianions since the DFT calculation does not make false predictions of stability.
Keywords: MULTIPLY-CHARGED ANIONS; TRIPLET CARBENE; LIFETIMES